#### Answer

$f(g(h(x)))=6x^2+1$

#### Work Step by Step

$f(x)=3x+4, g(x)=2x-1, h(x)=x^2$
$$f(g(h(x)))$$
$f(g(x^2))$
$f(2(x^2)-1)$
$f(2x^2-1)$
$3(2x^2-1)+4$
$6x^2-3+4$
$6x^2+1$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$f(g(h(x)))=6x^2+1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.